NIEMIECKOJĘZYCZNY ODBIÓR TEKSTÓW JULIANA TUWIMA. KILKA UWAG O TRUDNOŚCIACH TRANSLACYJNYCH / The Reception of Julian Tuwim’s Works in German-Speaking Countries. A Few Notes on Translation Problems - Doschek, Jolanta (Prace Polonistyczne, 2019)
The article responds to the need for a more comprehensive research on the reception and translation of Julian Tuwim’s diverse and innovative oeuvre outside Poland. More specifically, it discusses the reception of Julian Tuwim’s works among German-speaking readers. The author examines selected problems with translating Tuwim’s poetry into German, which are related to the structure and syntax of the poems. In particular, the article focuses on the creative use of declensional forms, which is hard to convey in German due to the fact that it lacks instrumental forms of nouns.